Ornamentasi Vokal pada Tarsul Kutai Kartanegara - Pratama, Zamrud Whidas; Setyoko, Aris; Arozaq, Fikri Yassar (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
One form of singing or chanting spread through cultural needs is a traditional song originating from Kutai Kartanegara called tarsul. This study aimed to obtain data about what vocal ornaments are contained in the Kutai tarsul. The theory used in this research is the theory of music presentation forms, ornamentation, and western music vocal techniques. A qualitative descriptive study was chosen by prioritizing the musicology approach. The data was collected by (1) literature study, (2) observation, (3) interviews, (4) documentation. The stages in analyzing data are (1) data reduction, (2) data presentation, (3) historiography writing, and (4) conclusions. Data clarification was again carried out using data triangulation techniques. The results showed two kinds of tarsul rhythms commonly used by petarsul, namely tarsul with one rhythm (low) and tarsul with a rhythm of two (high). In Kutai Kartanegara's tarsul, there are several ornaments. Many melismatic ornaments are found at the end of the melody of each part of the tarsul sentence. There are three forms of melismatic ornamentation named for easy classification: melismatic ornament A, melismatic ornament B, and melismatic ornament C. Apart from melismatic ornamentation, there is symbolic ornamentation on tarsul, namely trill ornamentation. Next is the morden ornamentation. More specifically, lower mordent ornamentation was found. Lastly is the use of grupetto ornamentation. From the transcription and tarsul analysis of rhythm patterns 1 and 2, it was found groupetto reverse turn ornamentation.